TANGGUNG JAWAB PEMERINTAH DESA DALAM MEWUJUDKAN AKUNTABILTAS PEMERINTAHAN: Studi Desa Kindang Kecamatan Kindang Kabupaten Bulukumba - Fathullah, Andi Irham; Alimuddin, Alimuddin (SIYASATUNA : JURNAL ILMIAH MAHASISWA SIYASAH SYAR'IYYAH, 2023)
This study aims to find out the description of village administration in Kindang Village in supporting government accountability. The type of research used is qualitative field research with a normative juridical approach. The results of the study show that the administration of government in Kindang Village is still far from the principles of good governance. Judging from the three main principles of good governance, namely the principle of participation, the principle of transparency, and the principle of accountability, the village government has not been able to implement it optimally. The obstacles that occur in the implementation of good village governance in Kindang Village are the lack of understanding regarding the main tasks and functions of the village government, the lack of coordination between the government and the Village Consultative Body and the existence of village community conflicts.